2016
DOI: 10.1515/romneu-2016-0026
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the recurrence rate of operated chronic subdural hematomas

Abstract: In this study we are trying to establish a correlation between the surgical technique used for the treatment of chronic subdural hematomas and the risk of recurrence. Between 01.06.2008 and 31.05.2014, 123 patients with 138 chronic subdural hematomas (CSDH) were operated on and followed-up in our department. Among them, 16 hematomas (11,6%) recurred. Factors related to the patients (gender, age, location of the hematoma) are analyzed as possible predictors of recurrence. Several surgical techniques were used i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…When cerebellar hemorrhage occurs with blood collections exceeding 3 cm in diameter or brainstem compression resulting in aggravating consciousness disturbance (Glasgow Coma Scale score ≤ 13), clot clearance should be applied before the condition of the patient deteriorates to relieve oppression and save life. If cerebellar hematoma exceeds 3 cm in diameter but the 4th ventricle is not totally obliterated, surgical clot removal may not be required and conservative treatment or ventricular drainage can be a feasible treatment [106][107][108] .…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…When cerebellar hemorrhage occurs with blood collections exceeding 3 cm in diameter or brainstem compression resulting in aggravating consciousness disturbance (Glasgow Coma Scale score ≤ 13), clot clearance should be applied before the condition of the patient deteriorates to relieve oppression and save life. If cerebellar hematoma exceeds 3 cm in diameter but the 4th ventricle is not totally obliterated, surgical clot removal may not be required and conservative treatment or ventricular drainage can be a feasible treatment [106][107][108] .…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…Several surgical techniques ranging from just twist drill tapping and aspiration to more invasive procedures including single burr-hole drainage, enlarged burr-hole (small craniectomy), multiple burr-holes drainage, and complex craniotomy (with or without membranectomy) (with or without subgaleal or subdural closed drainage system) were used. There is correlation between the rate of recurrence and the surgical technique employed [9]. An Indian study in 2005 reported success of treatment of CSDH with single burr hole craniostomy and irrigation [10].…”
mentioning
confidence: 99%